2022
DOI: 10.1016/j.molp.2021.09.006
|View full text |Cite
|
Sign up to set email alerts
|

CLE14 functions as a “brake signal” to suppress age-dependent and stress-induced leaf senescence by promoting JUB1-mediated ROS scavenging in Arabidopsis

Abstract: Leaf senescence is an important developmental process in the plant life cycle and has a significant impact on agriculture. When facing harsh environmental conditions, monocarpic plants often initiate early leaf senescence as an adaptive mechanism to ensure a complete life cycle. Upon initiation, the senescence process is fine-tuned through the coordination of both positive and negative regulators. Here, we report that the small secreted peptide CLAVATA3/ESR-RELATED 14 (CLE14) functions in the suppression of le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
43
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(44 citation statements)
references
References 75 publications
0
43
0
1
Order By: Relevance
“…As the largest group of such peptides, CLE plays a crucial role in regulating meristem activity in shoots and roots as well as in vascular tissues (Cock & McCormick, 2001; Fiers et al ., 2005; Ito et al ., 2006; Kondo et al ., 2006). Recently, CLE14 was found to delay age‐dependent and stress‐induced leaf senescence by enhancing JUB1‐mediated scavenge of reactive oxygen species in Arabidopsis (Zhang et al ., 2021). Here, we found that mutation of CLE42 led to premature senescence, whereas overexpression of CLE42 resulted in prolonged plant longevity (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…As the largest group of such peptides, CLE plays a crucial role in regulating meristem activity in shoots and roots as well as in vascular tissues (Cock & McCormick, 2001; Fiers et al ., 2005; Ito et al ., 2006; Kondo et al ., 2006). Recently, CLE14 was found to delay age‐dependent and stress‐induced leaf senescence by enhancing JUB1‐mediated scavenge of reactive oxygen species in Arabidopsis (Zhang et al ., 2021). Here, we found that mutation of CLE42 led to premature senescence, whereas overexpression of CLE42 resulted in prolonged plant longevity (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…As the largest group of such peptides, CLE plays crucial roles in regulating meristem activity in shoots and roots as well as in vascular tissues (Cock & McCormick, 2001; Fiers et al , 2005; Ito et al , 2006; Kondo et al , 2006). Recently, CLE14 was found to delay age-dependent and stress-induced leaf senescence by enhancing JUB1-mediated scavenge of reactive oxygen species (ROS) in Arabidopsis (Zhang et al, 2021b). Here, we found that mutation of CLE42 led to premature senescence, whereas overexpression of CLE42 resulted in prolonged plant longevity (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…S3). Interestingly, CLE14 also delays these factors-induced leaf senescence by governing H 2 O 2 homeostasis (Zhang et al, 2021b). These findings suggest that CLE14 and CLE42 regulate leaf senescence probably through similar pathways.…”
Section: Discussionmentioning
confidence: 99%
“…The method of qRT–PCR was described previously [ 32 ]. Arabidopsis ACTIN2 ( AT3G18780 ) [ 34 ] was used as the internal reference. The relative expression levels of genes were showed the ratio of gene to ACTIN2 .…”
Section: Methodsmentioning
confidence: 99%